2012
DOI: 10.1021/bi201532q
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Insulin-like Growth Factor I with 10–23 DNAzymes: 2′-O-Methyl Modifications in the Catalytic Core Enhance mRNA Cleavage

Abstract: Insulin-like growth factor I (IGF-I) and its cognate receptor (IGF-1R) contribute to normal cell function and to tumorigenesis. The role of IGF-I signaling in tumor growth has been demonstrated in vivo using nucleic acid-based strategies. Here, we designed the first 10-23 DNAzymes directed against IGF-I mRNA. Unlike antisense approaches and RNA interference that require protein catalysis, DNAzymes catalyze protein-free RNA cleavage. We identified target sequences and measured catalytic properties of differentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…7,15 Out of the two, the 10-23 DNAzyme has been widely studied for intracellular mRNA cleavage. 13,[16][17][18] This is probably because of its excellent substrate generality, it cleaves any purine/pyrimidine junctions, 7 which offers tremendous freedom to target many regions of interest within an mRNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 Out of the two, the 10-23 DNAzyme has been widely studied for intracellular mRNA cleavage. 13,[16][17][18] This is probably because of its excellent substrate generality, it cleaves any purine/pyrimidine junctions, 7 which offers tremendous freedom to target many regions of interest within an mRNA.…”
mentioning
confidence: 99%
“…For example, when an rAC junction was used, barely any cleavage was observed even with 500 mM Mg 2+ ( Figure S1, ESI). Therefore, it is also true for the [10][11][12][13][14][15][16][17][18][19][20][21][22][23] DNAzyme that its cleavage activity for every junction is not the same.…”
mentioning
confidence: 99%
“…Because deoxyribozymes generally exhibit little or no catalysis at the free divalent metal ion concentrations inside cells, efforts with modified deoxyribozymes are intended to improve in vivo catalysis [8085]. In one instance with otherwise-unmodified DNA, introducing 2′- O -methyl substitutions to improve 10–23 deoxyribozyme stability was accompanied by data supporting in vivo mRNA degradation [100]. However, broadly compelling evidence for in vivo DNA-catalyzed mRNA degradation is currently unavailable.…”
Section: Applications Of Deoxyribozymesmentioning
confidence: 99%
“…However, a majority of work where downregulation of gene expression was studied using inactive mutant Dzs as controls have shown that biological activity of Dzs could be unequivocally ascribed to their intrinsic ability to catalyze RNA cleavage in cells (see, e.g., [12][13][14][15][16][17][18][19][20][21]). Our understanding of the intracellular mechanism(s) of action of an oligonucleotide is crucial for successful nucleic acid drug design, in particular from the point of view of possible off-target effects.…”
Section: ′-N N N N N N N N N Y R N N N N N N N N N Nmentioning
confidence: 99%